Interprosthetic Joint Motion in Bipolar Partial Hip Arthroplasty After One-Year Follow-up - Noreen Joyce Yeo; Liberato Antonio Leagogo (Philippine Journal of Orthopaedics)
Background: Partial hip arthroplasty is the treatment of choice for displaced femoral fractures in the elderly. The bipolar prosthesis was developed to lessen the acetabular erosion encountered with the unipolar prosthesis. However, bipolar prostheses lose their motion between the inner or outer articulation (interprosthetic joint motion) after three months, rendering them biomechanically like unipolar prostheses. Literature has shown that the interprosthetic joint is mobile radiographically up to one year after the surgery.